Calibration of a numerical model for heat transfer and fluid flow in an extruder. (2016) - Hofstatter, Thomas; Pedersen, David Bue; Nielsen, Jakob S.; Pimentel, Rodrigo; Mischkot, Michael; Hansen, Hans NÁ¸rgaard
This paper discusses experiments performed in order to validate simulations on a fused deposition modelling (FDM) extruder. The nozzle has been simulated in terms of heat transfer and fluid flow. In order to calibrate and validate these simulations, experiments were performed giving a significant look into the physical behaviour of the nozzle, heating and cooling systems. Experiments on the model were performed at different sub-mm diameters of the extruder. Physical parameters of the model - especially temperature-dependent parameters - were set into analytical relationships in order to receive dynamical parameters. This research sets the foundation for further research within melted extrusion based additive manufacturing. The heating process of the extruder will be described and a note on the material feeding will be given.